Clinical study on the therapeutic effects of Quercus infectoria galls as oral powder in gingivitis and plaque patients - Ali Hasanain Alhamadani1 , Hiba Ahmed Saeed2 , Hussein Asli Khayoon3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Gingivitis is a nondestructive disease that causes inflammation of the gums and is one of the most commonperiodontal diseases. The cause of inflammation is bacterial bovillomatosis, known as the plaque, on thesurface of the teeth. The plaque is the main cause of periodontal disease; if left untreated, gingivitis candevelop into inflammation of the tooth, where inflammation of the gums destroys the bones, causes tissueerosion around the teeth and can lead to loss of tooth. Q. infectoria were applied topically to ten people aged25-55 who were suffering from gingivitis and plaque. Diagnoses and follow-up treatment were performed ina dental clinic under the supervision of a dentist for a period of two weeks. We noted the great efficacy of theherb against gingivitis and plaque. The progress of plaque measured in terms of mean, population standarddeviation and variance were 0.66 , 0.17, 0.02 before treatment and 0.29, 0.12, 0.01 after treatment. Gingivalprogress before and after treatment were 0.72 , 0.15 , 0.02 and 0.32 , 0.11 , 0.01 , respectively. Accordingto results were due to the fact that Q. infectoria contain large amounts of tannin and other compounds thatconstrict vessels and tissues and are effective against various types of infections. Therefore, we recommendthem as an alternative to antibiotics. Effectiveness of Q. infectoria as an effective substance to inhibit thegrowth of oral bacteria and thus act as an anti-inflammatory and retention of gum tissue where the substancewas tested directly on patients have Plaque and gingivitis and we can recommend them as an alternative toantibiotics